2011
DOI: 10.1002/jnr.22595
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophage migration inhibitory factor in primary glioblastoma multiforme cells

Abstract: Macrophage migration inhibitory factor (MIF) is a protein that is overexpressed in many tumors, such as colon and prostate cancer, melanoma, and glioblastoma multiforme (GBM). In its function as a cytokine, MIF induces angiogenesis, promotes cell cycle progression, and inhibits apoptosis. Recently, the molecular signal transduction has been specified: MIF has been found to be a ligand to the CD74/CD44-receptor complex and to activate the ERK1/2 MAPK cascade. In addition MIF binds to the chemokine receptors CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…Furthermore, our data confirmed worst prognosis for high-grade glioblastoma with high levels of CD74 expression. However, our data suggest that CD74 expression alone is not an independent marker for poor prognosis and it requires the expression of MIF for tumor pathogenesis, as previously reported in other studies (4,7,16,17,18) . Although we did not perform co-localization staining for MIF-CD74 in this retrospective study, evidence of MIF and CD74 co-localization reported in several other studies (7,8,9,10,11,12,13,14) .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, our data confirmed worst prognosis for high-grade glioblastoma with high levels of CD74 expression. However, our data suggest that CD74 expression alone is not an independent marker for poor prognosis and it requires the expression of MIF for tumor pathogenesis, as previously reported in other studies (4,7,16,17,18) . Although we did not perform co-localization staining for MIF-CD74 in this retrospective study, evidence of MIF and CD74 co-localization reported in several other studies (7,8,9,10,11,12,13,14) .…”
Section: Discussionsupporting
confidence: 77%
“…In line with this observation, we demonstrated overexpression of MIF in grade II-IV astrocytoma, and that overexpression of CD74 is associated with tumor progression in astrocytoma at the gene and transcription levels. MIF exerts multimodal functions in glioblastoma including pro-proliferative, promigratory, pro-angiogenic as well as immune-evasive properties through CD74 (16,17,18) . The binding of MIF to the extracellular domain of CD74 is necessary as an initial step in the MIF signaling cascade (4) resulting in tumor vascularization and the promotion of neoplastic Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MIF expression in GBM has been previously reported [51, 52], but its role in GBM-mediated immunosuppression is only beginning to be elucidated [53]. However, in other tumors MIF secretion is associated with increased intratumoral mMDSCs [54] and adding an inhibitor of MIF’s keto-enol tautomerase activity to tumor supernatant has decreased the formation of mMDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a previous study, a BrdU assay revealed that in glioblastoma cell lines treated with isoxazoline (ISO)-1, cell proliferation was inhibited in a concentration-dependent manner (42). Similarly, the use of MIF or CD74 neutralizing antibodies has been demonstrated to inhibit human prostate cancer cell (DU-145) proliferation (14).…”
Section: Mif and Cell Proliferation Shi Et Almentioning
confidence: 97%